Disruptions and Corporate Human Rights Responsibility - Winibaldus Stefanus Mere; Otto Gusti Ndegong Madung (University of Jember, 2022)
This article aims to examine the question of how and to what extent business entities can balance the necessities of making business profits and performing social responsibilities in spite of various disruptions encountered in a pandemic. How and to what extent should their social and human rights responsibilities be managed during the COVID-19 pandemic or a similar crisis? The relevance of these questions arises from the fact that while the main purpose of business is to make profits while providing goods, services, jobs, and sources of income to many people, various disruptions arising from policy responses to the COVID-19 pandemic have been posing very serious challenges to business management practices, profitability, and sustainability. These challenges may force businesses to compromise on their social and human rights responsibilities to affected stakeholders for the sake of preserving their commercial responsibilities to their shareholders. This article argues that efforts to ensure effective performance for a balanced approach between commercial responsibilities and human rights responsibilities require a corporate organizational culture that takes human rights risks as seriously as commercial risks. This means there must be an organizational attitude that maintains an unwavering commitment to respect human rights while doing business. In practice, this organizational attitude should be manifested through a clear indicator of its commitment to both â€œknow and â€œshowâ€ human rights responsibilities by way of embedding human rights policy and due diligence procedures into corporate culture. Keywords: Corporate human rights due diligence, disruptions, COVID-19, Pandemic, Business dilemma